A review of contemporary patterns of endemism for shallow water reef fauna in the Red Sea - Di Battista, Joseph; Roberts, M.; Bouwmeester, J.; Bowen, B.; Coker, D.; Lozano-Cortes, D.; Choat, J.; Gaither, M.; Hobbs, Jean-Paul; Khalil, M.; Kochzius, M.; Myers, R.; et al. (2015)
Aim: The Red Sea is characterised by a unique fauna and historical periods of desiccation, hypersalinity and intermittent isolation. The origin and contemporary composition of reef-associated taxa in this region can illuminate biogeographical principles about vicariance and the establishment (or local extirpation) of existing species. Here we aim to: (1) outline the distribution of shallow water fauna between the Red Sea and adjacent regions, (2) explore mechanisms for maintaining these distributions and (3) propose hypotheses to test these mechanisms. Location: Red Sea, Gulf of Aden, Arabian Sea, Arabian Gulf and Indian Ocean. Methods: Updated checklists for scleractinian corals, fishes and non-coral invertebrates were used to determine species richness in the Red Sea and the rest of the Arabian Peninsula and assess levels of endemism. Fine-scale diversity and abundance of reef fishes within the Red Sea were explored using ecological survey data. Results: Within the Red Sea, we recorded 346 zooxanthellate and azooxanthellate scleractinian coral species of which 19 are endemic (5.5%). Currently 635 species of polychaetes, 211 echinoderms and 79 ascidians have been documented, with endemism rates of 12.6%, 8.1% and 16.5% respectively. A preliminary compilation of 231 species of crustaceans and 137 species of molluscs include 10.0% and 6.6% endemism respectively. We documented 1071 shallow fish species, with 12.9% endemic in the entire Red Sea and 14.1% endemic in the Red Sea and Gulf of Aden. Based on ecological survey data of endemic fishes, there were no major changes in species richness or abundance across 1100 km of Saudi Arabian coastline. Main conclusions: The Red Sea biota appears resilient to major environmental fluctuations and is characterized by high rates of endemism with variable degrees of incursion into the Gulf of Aden. The nearby Omani and Arabian Gulfs also have variable environments and high levels of endemism, but these are not consistently distinct across taxa. The presence of physical barriers does not appear to explain species distributions, which are more likely determined by ecological plasticity and genetic diversity.